Aging, comorbidities, and the importance of finding biomarkers for HIV-associated neurocognitive disorders - Rosenthal, Jacqueline (J Neurovirol, 2019)
HIV associated neurocognitive disorders (HAND) continue to affect a large proportion of persons living with HIV despite effective viral suppression with combined antiretroviral therapy (cART). Importantly, milder versions of HAND have become more prevalent. The pathogenesis of HAND in the era of cART appears to be multifactorial with contributions from central nervous system (CNS) damage that occur prior to starting cART, chronic immune activation, cART neurotoxicity, and various age-related comorbidities (i.e. cardiovascular and cerebrovascular disease, Diabetes, hyperlipidemia). Individuals with HIV may experience premature aging, which could also contribute to cognitive impairment. Likewise, degenerative disorders aside from HAND increase with age and there is evidence of shared pathology between HAND and other neurodegenerative diseases, such as Alzheimer’s disease, which can occur with or without co-existing HAND. Given the aforementioned complex interactions associated with HIV, cognitive impairment, and aging, it is important to consider an age-appropriate differential diagnosis for HAND as the HIV positive population continues to grow older. These factors make the accuracy and reliability of the diagnosis of mild forms of HAND in an aging population of HIV-infected individuals challenging. The complexity of current diagnosis of mild HAND also highlights the need to develop reliable biomarkers. Ultimately, the identification of a set of specific biomarkers will be required to achieve early and accurate diagnosis, which will be necessary assuming specific treatments for HAND are developed.